2000
DOI: 10.1046/j.1365-2133.2000.03422.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of outcome of Mohs’ micrographic surgery for cutaneous squamous cell carcinoma using formalin fixed sections

Abstract: The surgical management of recurrent or large squamous cell carcinoma (SCC) can be challenging as tumours often extend beyond visible margins. Micrographic surgery is a potentially effective method of ensuring complete clearance of tumour. A retrospective study of all cases of SCC treated by micrographic surgery in this department between 1986 and 1996 has been done. Sixty-one patients were treated using a formalin-fixed paraffin-embedded tissue technique with a median follow-up of 4 years. In two cases there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 8 publications
0
45
0
4
Order By: Relevance
“…568 In a case series of 87 auricular SCCs, no distant metastases were reported during a mean follow-up period of 34.6 months. 571 One smaller series of 48 SCCs treated by MMS observed one patient with distant metastasis during a mean follow-up of 3.4 years, 567 and a further series including eight patients with periocular SCC also noted one patient with metastases to the lung; 564 however, the authors presumed that this patient had subclinical spread of tumour prior to treatment with MMS as there was no evidence of local recurrence.…”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…568 In a case series of 87 auricular SCCs, no distant metastases were reported during a mean follow-up period of 34.6 months. 571 One smaller series of 48 SCCs treated by MMS observed one patient with distant metastasis during a mean follow-up of 3.4 years, 567 and a further series including eight patients with periocular SCC also noted one patient with metastases to the lung; 564 however, the authors presumed that this patient had subclinical spread of tumour prior to treatment with MMS as there was no evidence of local recurrence.…”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%
“…568,572 Six studies reported recurrence in the regional lymph nodes after treatment with MMS. 545,564,565,567,569,573 On pooled analysis (comprising 1162 patients) the average regional recurrence was 4.2% (95% CI 2.3% to 6.6%; I 2 = 56%) ( Figure 37). There was no significant impact on regional recurrence in the sensitivity analysis, which included only four studies meeting the criteria, 545,565,567,569 with average recurrence of 3.2% (95% CI 1.9% to 5.0%, I 2 = 29%).…”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Permite a remoção completa do tumor com máxima preservação do tecido sadio peritumoral. [1][2][3][4][5][6][7][8][9][10] Na CMM são examinadas 100% das margens do tecido removido através da análise histopatológica por congelação. Código de cores e mapa são confeccionados para determinar a exata localização de um possível tumor residual.…”
Section: Introductionunclassified